Utilizing GIS cloud for monitoring and mosquito control - Cenaj, Erjola; Maraj, Elda; Kuka, Shkelqim (Edelweiss Applied Science and Technology, 2025)
The rise in mosquito-borne diseases highlights the urgent need for effective monitoring and control strategies. Geographic Information Systems (GIS), particularly in cloud environments, offer innovative solutions for pest management. As technology advances, the integration of GIS in pest control strategies will continue to evolve, paving the way for more effective and sustainable mosquito management practices. This article discusses the application of GIS Cloud in monitoring mosquito populations, its benefits, methodology, and a case study that illustrates its effectiveness in mosquito control. The public health department collected data from field surveys and integrated it within GIS Cloud. By using GIS Cloud, our users access the full power of desktop GIS, allowing for activities such as geospatial analysis, spatial intelligence, the creation of customized mapping reports, and publishing geographic analysis on the web. By analyzing spatial data, health officials could implement community programs to reduce breeding sites, leading to a significant decrease in mosquito populations in targeted areas.